2014
DOI: 10.1161/strokeaha.114.006662
|View full text |Cite|
|
Sign up to set email alerts
|

Grading and Interpretation of White Matter Hyperintensities Using Statistical Maps

Abstract: Background and Purpose-We aimed to generate rigorous graphical and statistical reference data based on volumetric measurements for assessing the relative severity of white matter hyperintensities (WMHs) in patients with stroke. Methods-We prospectively mapped WMHs from 2699 patients with first-ever ischemic stroke (mean age=66.8±13.0 years) enrolled consecutively from 11 nationwide stroke centers, from patient (fluid-attenuated-inversion-recovery) MRIs onto a standard brain template set. Using multivariable an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 47 publications
(37 reference statements)
5
74
0
Order By: Relevance
“…A large multicenter study of WMH in 2699 stroke patients in 11 stroke centers in China suggested that raised cholesterol was a more important risk factor for WMH in older hypertensive patients whereas age alone was the major risk factor in older non-hypertensive patients. Diabetes mellitus was an important risk factor in younger non-hypertensives 35. It is unclear as yet if hypertension has most of its effect directly on the brain, or if it results in systemic vascular stiffening, which in turn affects the brain white matter36,37 and cognition 38.…”
Section: Clinical Importancementioning
confidence: 99%
See 4 more Smart Citations
“…A large multicenter study of WMH in 2699 stroke patients in 11 stroke centers in China suggested that raised cholesterol was a more important risk factor for WMH in older hypertensive patients whereas age alone was the major risk factor in older non-hypertensive patients. Diabetes mellitus was an important risk factor in younger non-hypertensives 35. It is unclear as yet if hypertension has most of its effect directly on the brain, or if it results in systemic vascular stiffening, which in turn affects the brain white matter36,37 and cognition 38.…”
Section: Clinical Importancementioning
confidence: 99%
“…Some studies differentiate periventricular from deep WMH12,76,77 although imaging studies indicate that periventricular and deep WMH are probably mostly part of a continuous pathology 76,78. A recent very large study in 2699 patients with stroke from 11 stroke centers in China created statistical maps of WMH distribution and provided more evidence to support treating periventricular and deep WMH as a continuous pathology, any apparent difference in distribution in some patients simply reflecting an earlier stage in disease 35. Notwithstanding, the available pathology describes periventricular WMH as having discontinuous ependyma, gliosis, loosening of the white matter fibers, and myelin loss around tortuous venules in perivascular spaces,11,12,79 the gliosis, demyelination, and fiber loss worsening as the periventricular WMH worsened.…”
Section: What Do Pathology Studies Suggest That Wmh Are Due To?mentioning
confidence: 99%
See 3 more Smart Citations